The Influence of Digitalization in Improving the Integrity and Ethics of the Notary Profession - Aulia Syifa Sjamhars; Pujiyono Pujiyono (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Digitalization has become a strategic step to enhance the integrity and ethics of the notary profession in the globalization era. Technologies such as electronic signatures and cloud-based document management systems improve security, transparency, and accountability. Using a normative juridical approach, this study analyzes the impact of digitalization on the notary profession and identifies challenges such as technological infrastructure, digital literacy, and regulatory gaps. Proposed solutions include improving infrastructure, digital training, regulatory updates, and data security. The findings show that digitalization strengthens public trust through safer, more efficient, and transparent document management.